Relationship between enterprise digitalization and green innovation: A mediated moderation model - Jing Ning; Xinyuan Jiang; Junmei Luo (Journal of Innovation & Knowledge (JIK), 2023)
Faced with increasingly severe environmental challenges and the rapid development of digital technologies, enterprises' green innovation and digitalization strategies have attracted much attention. However, research that links green innovation with enterprise digitalization and explores the internal mechanism of this link is still scant. Therefore, based on the dynamic capability theory and capability hierarchy, this study develops and examines a conceptual model that describes the digitalization-green innovation relationship. Using data covering 1,166 listed manufacturing firms in China during 2008-2019, we apply the ordinary least squares method to verify that enterprise digitalization can positively affect green innovation, and absorptive capacity mediates this relationship. Moreover, we find that green credit strengthens the positive relationship between absorptive capacity and green innovation. Based on these findings, this study provides valuable theoretical reference and practical enlightenment for promoting green innovation more effectively.
Keywords: O32; 650; Absorptive capacity; Enterprise digitalization; Green credit; Green innovation